1996
DOI: 10.1074/jbc.271.44.27645
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Distinct Assembly Forms of Immunoglobulin M Occurs in Multiple Sites in Permeabilized B Cells

Abstract: Protein degradation is essential for quality control which retains and eliminates abnormal, unfolded, or partially assembled subunits of oligomeric proteins. The localization of this nonlysosomal pre-Golgi degradation to the endoplasmic reticulum (ER) has been mostly deduced from kinetic studies and carbohydrate analyses, while direct evidence for degradation within the ER has been provided by in vitro reconstitution of this process. In this article, we took advantage of the transport incompetence of permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 62 publications
1
21
1
Order By: Relevance
“…4). The fact that H-L disassembly requires energy might explain why the degradation of assembled s was facilitated by cytosolic factors and reducing agents to a greater extent than free chains (26,27). Our data do not allow us to establish whether also intrachain disulfides are reduced before dislocation of Ig subunits as suggested for major histocompatibility complex class I heavy chains (42).…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…4). The fact that H-L disassembly requires energy might explain why the degradation of assembled s was facilitated by cytosolic factors and reducing agents to a greater extent than free chains (26,27). Our data do not allow us to establish whether also intrachain disulfides are reduced before dislocation of Ig subunits as suggested for major histocompatibility complex class I heavy chains (42).…”
Section: Discussioncontrasting
confidence: 39%
“…For reasons that are still unclear, IgM polymerization is inefficient in B cells (24). Therefore, most s chains are retained and eventually degraded despite assembling with L chains to form s2 ⅐L 2 complexes (25)(26)(27)(28). In contrast, analogous complexes containing membrane chains ( m2 ⅐L 2 ) negotiate assembly with signaling components (Ig-␣ and Ig-␤) and are transported to the cell surface of B lymphocytes (29,30) where they act as antigen receptors.…”
Section: The Endoplasmic Reticulum (Er)mentioning
confidence: 99%
“…Based on its stabilization by a variety of proteasome inhibitors, we and others have shown that s is degraded by the proteasome (9,18,19). Moreover, in B lymphocytes treated with proteasome inhibitors, we were able to detect ubiquitinated species of s ( Fig.…”
Section: Resultsmentioning
confidence: 51%
“…The luminal s heavy chain exhibits developmentally regulated stability; while being a stable protein that is secreted efficiently from plasma cells, it is degraded rapidly in the earlier differentiation stages of pre-B and B cells (19,24,30). Based on its stabilization by a variety of proteasome inhibitors, we and others have shown that s is degraded by the proteasome (9,18,19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation